A second dose of a measles-mumps-rubella vaccine administered to healthy four-to-six-year-old children: a phase III, observer-blind, randomized, safety and immunogenicity study comparing GSK MMR and MMR II with and without DTaP-IPV and varicella vaccines co-administration - The MMR-158 Study Group (Taylor & Francis Group, 2019)
In many countries, a second dose of a combined measles, mumps, and rubella (MMR) vaccine is recommended at 4-6 years of age - similarly to the booster of diphtheria, tetanus, acellular pertussis, and inactivated polio vaccine (DTaP-IPV) and the second dose of varicella vaccine (VV). Vaccine co-administration is generally encouraged if no interferences exist among the vaccines. This phase IIIa, randomized, controlled trial (NCT01621802) evaluated the immunogenicity and safety of MMR-RIT (Priorix, GSK) when given as a second dose with or without co-administration of DTaP-IPV and VV, using MMR II (M-M-R II, Merck & Co Inc.) as comparator. Antibody geometric mean concentrations or titers (GMCs/GMTs) and response rates to the components of all the administered vaccines were assessed. Solicited, unsolicited, and serious adverse events were recorded. Four thousand eleven children aged 4-6 years were enrolled. MMR-RIT elicited immune responses that were not inferior to those of MMR II in terms of GMCs and seroresponse rates when administered alone or when co-administered with DTaP-IPV and VV. The immune responses to the co-administered vaccines in MMR-RIT recipients were non-inferior to those in MMR II recipients. MMR-RIT and MMR II demonstrated similar reactogenicity profiles; the most frequent solicited adverse events across vaccine groups and sub-cohorts were local pain and fever. In conclusion, the immunogenicity and safety profiles of MMR-RIT administered with or without DTaP-IPV and VV were similar to those of MMR II.